Comparison of analytical and numerical models in predicting the yield of an infiltration gallery a case study of Dacanlao raw water intake in Calaca, Batangas - Macuha, Richmark N.; Tabios, Guillermo Q. III (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
An infiltration gallery is a horizontal well or group of horizontal wells that transmit water to or from underground source. For water supply purposes, the infiltration gallery has significant advantage in terms of quantity and quality over traditional vertical wells and surface water intakes in some specific instances. However, in the Philippines, it is rarely considered in water resources development, partially because of limited technical guidelines to design and evaluate such an intake structure. The main purpose of this study is to compare, evaluate and examine the applicability of available tools and models in predicting the yield of existing infiltration galleries. Three (3) modeling methodologies were considered to estimate the yield of an existing infiltration gallery. These models are: a 1-D Steady Seepage Model, the most-widely used yield estimation technique in the local industry; the 2-D Potential Flow Model, an approximate analytical solution; and the 3-D MODFLOW model, the current state of the art in saturated groundwater numerical modeling. Prior to comparison, hydrologic, hydraulic and hydrogeological data were collected and assessed. Then, the yield from the infiltration gallery was estimated, obtaining primary yield ranging from 2.32-19.53 MLD (million liters per day). As compared to actual measured flow, the average deviation from actual measured flows are -86.59% for the 1-D Model, -18.83% for the 2-D Model and +8.14% for the 3-D Model. Although the yield can be rapidly estimated with minimal data requirements using the 1-D Model, it largely underestimates the actual flow mainly because it excludes the effect of groundwater interaction to the bulk of the flow pattern covered by the infiltration gallery. The 2-D and 3-D models are proven to be satisfactory, but with different levels of complexity, implementation and data requirements as illustrated in this study.
Thesis (M.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Wells -- Philippines; Horizontal wells; Horizontal infiltration galleries